The Representation of The Judge Muhammad Daming Sunusi On His Controversial Statement: A Critical Discourse Analysis on Indonesian Online Newspapers - Riestia Handayati (Passage, 2014)
News tends to be manipulated by some people to control over other people because news shapes publics opinions. Nowadays people can share news content easily in internet because internet becomes space where people can connect, communicate, and share everything easily. In line with that, this present research examined the representation of Muhammad Daming Sunusi concerning his controversial statement “women enjoy being raped” as evidenced in Indonesian Online Newspapers by using Sociosemantic approach from van Leeuwen (2008). This research employed descriptive qualitative method to describe the representation and its significance. The collected data were 6 online articles taken from Detik, Kompas, and Tribunnews. The data were analyzed in the unit of words, phrases, and sentences to reveal the representation of Muhammad Daming Sunusi concerning his controversial statement. This research disclosed that, according to the text, Muhammad Daming Sunusi was represented as the one who should be responsible of his statement and he was also represented in a negative way since his case was considered as an insult to the rape victims. Hence, by sociosemantic and context analysis, the research revealed that Detik, Kompas, and Tribunnews had the same pattern and thought in representing Muhammad Daming Sunusi.Keywords: Critical Discourse Analysis, Sociosemantic, Van Leeuwen, Representation, Muhammad Daming Sunusi